The The Role of Financial Knowledge in Moderating the Effect of Entrepreneurial Leadership on Financial Performance in the Creative Industry in Gianyar Regency - Ida Ayu Dinda Priyanka MAHARANI; Ida Bagus Gde Indra Wedhana PURBA (International Journal of Environmental, Sustainability, and Social Science, 2025)
The creative industry is one form of business that plays a role in supporting the tourism sector. However, the creative industry faces challenges in maintaining its financial performance. Strategies are needed to encourage improved financial performance in the creative industry, utilizing the concepts of entrepreneurial leadership and financial knowledge. The integration of entrepreneurial leadership and financial knowledge provides new insights into improving the financial performance of the creative industry. The purpose of this study is to analyze the influence of entrepreneurial leadership on financial performance and examine the moderating role of financial knowledge in this relationship. This research employs quantitative methods, and the research procedure employed a questionnaire. The sample in this study was the creative industry (wood craft and craft industries) in Gianyar Regency. The sample size was 35. The collected data were processed using structural equation modeling (SEM) based on partial least squares (PLS).